Signal transduction through homologs of the Ste20p and Ste7p protein kinases can trigger hyphal formation in the pathogenic fungus Candida albicans - Leberer, Ekkehard (The National Academy of Sciences of the USA, 1996)
The CST20 gene of Candida albicans was cloned by functional complementation of a deletion of the STE20 gene in Saccharomyces cerevisiae. CST20 encodes a homolog of the Ste20p/p65(PAK) family of protein kinases. Colonies of C. albicans cells deleted for CST20 revealed defects in the lateral formation of mycelia on synthetic solid “Spider” media. However, hyphal development was not impaired in some other media. A similar phenotype was caused by deletion of HST7, encoding a functional homolog of the S. cerevisiae Ste7p protein kinase. Overexpression of HST7 partially complemented the deletion of CST20. Cells deleted for CST20 were less virulent in a mouse model for systemic candidiasis. Our results suggest that more than one signaling pathway can trigger hyphal development in C. albicans, one of which has a protein kinase cascade that is analogous to the mating response pathway in S. cerevisiae and might have become adapted to the control of mycelial formation in asexual C. albicans.